Mobile Manipulation and Mobility as Manipulation—Design and Algorithms of RoboSimian. Issue 2 (March 2015) - Hebert, Paul; Bajracharya, Max; Ma, Jeremy; Hudson, Nicolas; Aydemir, Alper; Reid, Jason; Bergh, Charles; Borders, James; Frost, Matthew; Hagman, Michael; Leichty, John; Backes, Paul; et al.
<x xml:space="preserve">Abstract</x> This article presents the hardware design and software algorithms of RoboSimian, a statically stable quadrupedal robot capable of both dexterous manipulation and versatile mobility in difficult terrain. The robot has generalized limbs and hands capable of mobility and manipulation, along with almost fully hemispherical three‐dimensional sensing with passive stereo cameras. The system is semiautonomous, enabling low‐bandwidth, high latency control operated from a standard laptop. Because limbs are used for mobility and manipulation, a single unified mobile manipulation planner is used to generate autonomous behaviors, including walking, sitting, climbing, grasping, and manipulating. The remote operator interface is optimized to designate, parametrize, sequence, and preview behaviors, which are then executed by the robot. RoboSimian placed fifth in the DARPA Robotics Challenge Trials, demonstrating its ability to perform disaster recovery tasks in degraded human environments.